Bahasa Sebagai Penjaga Warisan Budaya: Studi pada Bahasa Daerah di Indonesia - Fikri Alamsyah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Background: Language acts as a vessel of cultural heritage, reflecting the values, history, and identity of communities. Regional languages in Indonesia are under threat due to language shift toward national or global languages. Sociolinguistic awareness is essential to preserve intangible cultural heritage. Purpose: This literature review aims to examine how sociolinguistic approaches in language education—particularly in teaching regional Indonesian languages—can enhance student communicative competence while preserving cultural identity. Methods: A descriptive‑qualitative methodology was employed. Using a literature review approach, academic documents (journals, books, proceedings) from sources such as Google Scholar were identified and analyzed. Thematic content analysis was used to extract key patterns, concepts, and findings. Main Findings: Implementation strategies include authentic discourse analysis, role‑play simulations, and discussions of language variation. These practices help learners appreciate register differences, politeness norms, and contextual language use. Students who engage in these activities exhibit improved pragmatic and sociocultural competence. They also develop greater awareness of linguistic variation and cultural norms. Conclusion: The study underscores the critical role of sociolinguistics as a bridge between linguistic knowledge and real‑world communicative ability. Integrating sociolinguistic principles into language teaching supports both heritage language preservation and the development of communicative competence.